2008
DOI: 10.1111/j.1530-0277.2008.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Typography Established by Scheduled Induction Predicts Chronic Heavy Drinking in a Monkey Model of Ethanol Self‐Administration

Abstract: Background-We have developed an animal model of alcohol self-administration that initially employs schedule-induced polydipsia (SIP) to establish reliable ethanol consumption under open access (22 h/d) conditions with food and water concurrently available. SIP is an adjunctive behavior that is generated by constraining access to an important commodity (e.g., flavored food). The induction schedule and ethanol polydipsia generated under these conditions affords the opportunity to investigate the development of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
338
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(348 citation statements)
references
References 37 publications
10
338
0
Order By: Relevance
“…Notably, we found that rapamycin attenuates "binge-like" alcohol drinking behavior. This last finding is of particular interest because binge drinking is an increasingly prevalent problem during adolescence and young adulthood, and is a strong predictor of future alcohol-related problems (40,41). Our findings are also relevant for the treatment of alcoholism, in which the pattern of alcohol consumption is often characterized by successive cycles of daily episodes of binge drinking and withdrawal (25).…”
Section: Discussionmentioning
confidence: 81%
“…Notably, we found that rapamycin attenuates "binge-like" alcohol drinking behavior. This last finding is of particular interest because binge drinking is an increasingly prevalent problem during adolescence and young adulthood, and is a strong predictor of future alcohol-related problems (40,41). Our findings are also relevant for the treatment of alcoholism, in which the pattern of alcohol consumption is often characterized by successive cycles of daily episodes of binge drinking and withdrawal (25).…”
Section: Discussionmentioning
confidence: 81%
“…One important feature of AAA models is the definition of biologically meaningful levels of alcohol, either in vitro or in vivo, and their relationship to blood alcohol levels (BAL) in humans. This is an important requirement of the research models of AAA, because BAL can be detected as soon as minimal amounts of alcohol are ingested [85] , however measurable affects of alcohol on physiology and/or behavior is established at 0.08% or above this level, with individual variations depending on the species, metabolic particularities, age, gender and genetic background [86][87][88][89][90][91][92][93][94][95][96][97] . It is also important to identify that AAA models differ by their route of alcohol delivery to achieve alcohol intoxication, some of them being physiological, such as oral administration, while others being non-physiological, when ethanol is administered by parenteral routes.…”
Section: Models Of Aaamentioning
confidence: 99%
“…Among non-human vertebrates commonly involved in alcohol research are primates [90,91,148] , pigs [104,120] , dogs [114,121] , mice [70,72,74,86,89,96,109,118,119,141] , rats [88,94,108,149,150] and rabbits [132] . The rodent AAA models (mice and rats) are used most frequently due to their relatively well-defined genetic background and the availability of diverse genetic traits, including those coding for high or low alcohol consumption [88,89,96,109] .…”
Section: Non-human Aaa Modelsmentioning
confidence: 99%
“…Dams were trained to orally selfadminister either 1.5g/kg/day of 4% ethanol solution (equivalent to 6 drinks/day) or an isocaloric control fluid following a previously described 4-month schedule induced polydipsia procedure 20,21,23 . Following drinking induction, plasma estradiol and progesterone levels were sampled daily until ovulation was suspected, at which point dams were paired with male animals.…”
Section: Experimental Designmentioning
confidence: 99%
“…Maternal smoking, nutritional inadequacy, medication or illicit drug use, all factors that can have a synergistic effect on alcohol exposure, often confound human studies of placental impairment. Modeling human drinking behavior with NHP models provides the added advantage of a precise alcohol history 20,21 while retaining the normal route of alcohol administration as opposed to strategies used to study fetal ethanol exposure in rodents. Further, voluntary ethanol selfadministration also obviates the need for procedures such as gavage, which introduce confounds associated with increased maternal stress 22 .…”
Section: Introductionmentioning
confidence: 99%